Factors influencing the financing behavior of large professional households engaged in green agricultural production in China - Zhong, Shen; Xu, Xueting; Li, Junwei; Wu, Nanlin (Frontiers in Psychology, 2023)
Green agriculture is the direction of sustainable development of China’s modern agriculture and the inherent requirement of taking the road of characteristic new agricultural modernization. As one of the main bodies of new agricultural management, professional large households are of great significance to lead the development of efficient agriculture and accelerate the development of green agricultural economy in Heilongjiang.Therefore, based on the theory of planned behavior, this paper takes 275 major professional households in Heilongjiang Province as a sample of demonstration counties (cities) for green, high-quality and efficient creation, combined with field research data and structural equation model, and discusses the willingness of large professional households to participate in green agricultural production financing. and behavioral factors and mechanisms of action.The perceived behavior control (PBC), attitude toward the behavior (AB) and subjective norms (SN) of large professional households to engage in green agricultural production determine their financing intentions (FN), which further determines their financing behavior (FB). The results show that PBC, AB and SN have a significant positive impact on the FN of large professional households, and further indirectly affect the FB. It should note that SN have the most significant impact on the FN of large professional households to participate in green agricultural production. Therefore, it is necessary to establish effective government propaganda measures and preferential policies, improve the awareness of the importance of green agricultural production financing, and create a good social atmosphere for agricultural sustainable development and active participation in financing. The purpose of this study is to provide a reference for policy makers to formulate relevant policies to cultivate major professional households and develop green agricultural economy in Heilongjiang province.